Quiet Cutting as Covert Workforce Restructuring: Implications for Human-Centered HRM - Prasetyanto, Alfian Dwi (Generate Digital Publishing, 2025)
Objective: This study aims to examine the phenomenon of quiet cutting as a form of covert workforce restructuring and analyze its implications for employment relationships from a human-centered HRM perspective. Research Design & Methods: This study uses a Systematic Literature Review (SLR) approach based on the PRISMA 2020 protocol by analyzing 124 articles indexed in Scopus, Web of Science, and ScienceDirect for the period 2020–2025. Data were analyzed using thematic analysis to identify conceptual patterns, relational mechanisms, and psychological and ethical implications of covert restructuring practices. Findings: The results of the study show that quiet cutting has not been discussed explicitly, but is manifested through practices such as job downgrading, redeployment, and role ambiguity. The main findings identify four themes: (1) implicit restructuring as an organizational strategy, (2) psychological contract breach as a key mechanism, (3) erosion of trust and employee behavior impact, and (4) ethical dilemmas in the human-centered HRM framework. These practices have been shown to trigger cumulative psychological consequences and have a systemic impact on organizations. Implications & Recommendations: Organizations need to prioritize transparency, procedural fairness, and open communication in the restructuring process. HRM practices must be directed towards a human-centered approach to maintain trust and the sustainability of working relationships. Contribution & Value Added: This research contributes by integrating the phenomenon of quiet cutting into the theoretical framework of HRM and offers new insights into workforce restructuring as a relational and ethical process.